Pengaruh Tingkat Pendidikan Orang Tua Terhadap Prestasi Belajar Siswa di Moderasi oleh Fasilitas Belajar Pada SMP Negeri 2 Halmahera Barat - Emi Saribu (Peneliti.net, 2021)
This study has several objectives including: (1) Analyzing and knowing how the influence of parental education level on student learning achievement (2) analyzing and knowing how learning facilities moderate the relationship between parental education level on student learning achievement. This study used a quantitative method. There are several research subjects including: second grade students of SMP Negeri 2 West Halmahera and their parents. A total of 135 respondents were involved in this study, using the population method as a whole, second grade students of SMP Negeri 2 Halmahera Barat. This study has the following results: (1) Positive and significant influence on the level of parental education on student achievement. (2) Learning facilities have no effect on the relationship between the level of parental education on student achievement.